Relationship between Place strategy and Organizational Performance of Maize Seed Companies in Kenya - Jelimo, Nancy; Jemaiyo, Beatrice; Nyiva, Mary (British Journal of Marketing Studies, 2024)
The main purpose of the study was to evaluate relationship between place strategy and organizational performance of maize seed companies in Kenya. The study was guided by Marketing Mix Theory. This study adopted correlational research design. The sample size was 286 respondents (114 Marketing & 172 Sales officers). Data collection instrument was questionnaires. The data collected was analyzed using descriptive and inferential statistics. The study results showed that place strategy has a positive and statistically significant effect on organizational performance of maize seed companies in Kenya with (r=0.674; p<0.05). In conclusion Maize seed companies in Kenya use place strategy to improve organizational performance. Most of the maize seed company’s stores are strategically located to ensure consumers can easily access and purchase company products. The study recommends that the Ministry of Agriculture restructure maize seed distribution retail stores, as many of these stores are located far from local customers.